2021
DOI: 10.3390/diagnostics11091628
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Improves Hepatic Metabolic Dysfunctions in Acute Intermittent Porphyria: A Proof-of-Concept Study

Abstract: Background: Acute intermittent porphyria (AIP) is caused by the haploinsufficiency of porphobilinogen deaminase (PBGD) enzymatic activity. Acute attacks occur in response to fasting, and alterations in glucose metabolism, insulin resistance, and mitochondrial turnover may be involved in AIP pathophysiology. Therefore, we investigated the metabolic pathways in PBGD-silenced hepatocytes and assessed the efficacy of an insulin mimic, α-lipoic acid (α-LA), as a potential therapeutic strategy. Methods: HepG2 cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Disturbances in glucose metabolism associated with PBGD deficiency were also recently revealed by our group. We found that PBGD-mRNA silencing in human hepatoma cells (HepG2), especially during fasting stimulus, reduced the expression of glycolytic enzymes such as glucokinase (GCKR), phosphofructokinase (PFK) and pyruvate kinase (PK), suggesting that the downregulation of heme biosynthesis may even affect glycolysis [17].…”
Section: Impaired Glucose Homeostasis and Ir Contribute To Acute Atta...mentioning
confidence: 99%
See 4 more Smart Citations
“…Disturbances in glucose metabolism associated with PBGD deficiency were also recently revealed by our group. We found that PBGD-mRNA silencing in human hepatoma cells (HepG2), especially during fasting stimulus, reduced the expression of glycolytic enzymes such as glucokinase (GCKR), phosphofructokinase (PFK) and pyruvate kinase (PK), suggesting that the downregulation of heme biosynthesis may even affect glycolysis [17].…”
Section: Impaired Glucose Homeostasis and Ir Contribute To Acute Atta...mentioning
confidence: 99%
“…The impairment of mitochondrial bioenergetics could even be influenced by the unbalancing of the mitochondrial lifecycle and turnover, including fusion, fission, and mitophagy, which leads to alterations in mitochondrial dynamics, mass, shape, and metabolism. It was observed in both AIP mice and humans that the derangement of mitochondrial biogenesis was correlated with aberrations in mitochondrial morphology and functionality [17,52,54,56]. The analysis of the hepatic transcriptome of AIP mice, after PB exposure, indicated that the majority of differentially expressed genes belong to mitochondrial biogenesis and OXPHOS, both regulated by the peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PPARGC1A, encoding the PGC1-α transcription factor).…”
Section: The Occurrence Of Mitochondrial Failure In Aip Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations